Warren Buffett the world's greatest money maker - Miller, Charles (Australia : BBC, 2009)
Examines Buffett's business strategies as well as the high and low points of his career. This film reveals his business strategy - and tells the extraordinary story of his achievement
Title from title screen
Executive producer, Dominic Crossley-Holland
DVD format
Keywords: Buffett, Warren; Investments -- United States; Capitalists and financiers -- United States -- Biography